A BRIEF REVIEW ON RECENT DEVELOPMENTS AND EXPLORING ACTIVITIES OF 4-THIAZOLIDINONE - B, Arunlal V.; K., Vandana; R., Biju C. (International Journal of Current Pharmaceutical Research, 2015)
The present article is sincere attempt to review chemistry, synthesis, and applications of 4-thiazolidinone. Thiazolidinone, a saturated form of thiazole with carbonyl group on fourth carbon, has been considered as a magic moiety (wonder nucleus) which posses almost all types of biological activities. It belongs to an important group of heterocyclic compounds containing sulfur and nitrogen in a five-member ring. This biologically active scaffold has encouraged our interest in synthesizing several new compounds by using several substitutions at different positions, attached to 4-thiazolidinone moieties [1]. Thiazolidinone scaffolds are reviewed extensively in literature for its vibrant potential against several activities. The various substituted 4-thiazolidinone has shown a wide spectrum of biological activities. The literature reveals that 4-thiazolidinone has diverse biological potential, and the easy synthetic routes for synthesis have taken attention of the chemists, pharmacologists and researchers. By the present scenario it can be concluded that 4-thiazolidinones have a great potential which remain to be disclosed till date. Keywords: Thiazolidinone, Thiazole, Pharmacological activities.